impact, importance, types, and use of non-verbal communication in social relations - Grillo, Helena Mukli; Enesi, Miranda (Linguistics and Culture Review, 2022)
The problem of today's social and economic developments is based on communicative relations, which are the main factor in the development of human society. Most of all, the recent changes in communication reports proved how important communication is in achieving the goals not only of the speaker but also of society. Human society's important means of communication in all its types and dimensions, the relationship and mutual influence of these types are becoming more and more obvious. Over the years, different language schools have dealt with different approaches on the importance, cognition, and functionality of communication, not only linguistic but also non-linguistic, communication that does not rely on different grammatical tools and forms, or structured language, but also on the linguistic, or nonverbal element. Today's controversies in linguistics raise issues of meaning and significance, which often come from questions: 'What does it mean? 'However, the concept of meaning is not confused with communication. When we talk about communication, we refer to the process through which, someone conveys something, to someone else. The full realization of this process includes not only linguistic factors but also social and cultural ones.